2020
DOI: 10.1520/jte20170707
|View full text |Cite
|
Sign up to set email alerts
|

Run Sum Chart for the Mean with Auxiliary Information

Abstract: The use of the auxiliary information (AI) method in control charts is gaining increasing attention. Many studies have shown that auxiliary information-based charts can boost the charts’ performances in the detection of out-of-control signals. In this study, a run sum chart for the mean based on auxiliary characteristics (abbreviated as the RS-AI chart) is proposed. The optimization designs of the RS-AI chart in minimizing the steady-state out-of-control average run length (ARL) and expected average run length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The EARL1 formula in Equation () integrates over the distribution function fδfalse(δfalse) for the interval (δmin,δmax), where δmin and δmax denote the lower and upper bounds of the shift sizes in the process mean, respectively. As the exact shape of fδfalse(δfalse) is often hard to be identified due to insufficient information about the distribution of δ , the process mean shifts are assumed to be uniformly distributed over the interval (δmin,δmax), that is, the occurrence probability for each value of δ in the interval (δmin,δmax) is assumed to be equal 7,18 . Consequently, the EARL1 formula in Equation () becomes EARL1=1δmaxδminδminδmaxARL1()δ,L,n,kdδ.The in‐control EARL (EARL0) value is set to be similar to the ARL 0 value to ensure that both measures of performance have a similar in‐control run length performance.…”
Section: Auxiliary Information Based Side Sensitive Group Runs (Ssgr‐ai) Chartmentioning
confidence: 99%
See 2 more Smart Citations
“…The EARL1 formula in Equation () integrates over the distribution function fδfalse(δfalse) for the interval (δmin,δmax), where δmin and δmax denote the lower and upper bounds of the shift sizes in the process mean, respectively. As the exact shape of fδfalse(δfalse) is often hard to be identified due to insufficient information about the distribution of δ , the process mean shifts are assumed to be uniformly distributed over the interval (δmin,δmax), that is, the occurrence probability for each value of δ in the interval (δmin,δmax) is assumed to be equal 7,18 . Consequently, the EARL1 formula in Equation () becomes EARL1=1δmaxδminδminδmaxARL1()δ,L,n,kdδ.The in‐control EARL (EARL0) value is set to be similar to the ARL 0 value to ensure that both measures of performance have a similar in‐control run length performance.…”
Section: Auxiliary Information Based Side Sensitive Group Runs (Ssgr‐ai) Chartmentioning
confidence: 99%
“…In practice, the exact size of the shift is usually unknown due to inadequate historical data, coupled with the fact that the size of the shift tends to vary according to certain unknown stochastic models 18 . Hence, there is a possibility that a quality practitioner will compute the optimal parameters based on a wrongly specified size of the shift.…”
Section: Numerical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haq and Khoo (2016) proposed a synthetic control chart with auxiliary information (SYN-AI). Meanwhile, Ng et al (2018) proposed the run sum chart with auxiliary information (RS-AI) and showed that the RS-AI chart outperforms the SH-AI, SYN-AI and EWMA-AI charts for all shifts given that the correlation ρ is large. Saha et al (2018) developed the VSSI chart with auxiliary information (VSSI-AI) which surpasses the EWMA-AI and SYN-AI charts.…”
Section: Introductionmentioning
confidence: 99%
“…Haq and Khoo (2018) proposed a DS chart using AI while a VSSI chart using AI was presented by Saha et al (2019). Additionally, Ng et al (2018) presented the AI-based run sum (RS-AI) chart.…”
Section: Introductionmentioning
confidence: 99%